2023
DOI: 10.3390/cancers15153941
|View full text |Cite
|
Sign up to set email alerts
|

Survival after Pure (Acute) Erythroid Leukemia in the United States: A SEER-Based Study

Abstract: Background: Acute erythroid leukemia (AEL), also known as pure erythroid leukemia, is a rare subtype of acute myeloid leukemia (AML) characterized by the proliferation of malignant erythroid precursors. Outcome data at the population level are scarce. Methods: We performed a retrospective analysis of the Surveillance Epidemiology and End Results (SEER) database. All cases with a histologically confirmed diagnosis of acute (pure) erythroid leukemia during the period of 2000–2019 were included in the study. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 34 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…However, this classification appears to lack uniqueness, as the clinical features of TP53 -mutated AML are much broader than the pure erythroid leukemia, which are more homogeneous. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…However, this classification appears to lack uniqueness, as the clinical features of TP53 -mutated AML are much broader than the pure erythroid leukemia, which are more homogeneous. [ 15 ]…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a recent study showed that de novo AEL is associated with a better median survival (3.9 months) compared to patients with a history of MDS (2.6 months) or therapy-related AEL (2.3 months) [ 14 ]. The study notes that secondary AEL is characterized by a high incidence of refractory disease and early resistance to the current standard treatments, thereby leading to worse outcomes [ 15 ]. It should be highlighted that these conclusions are almost exclusively based on the former WHO/ICC categories.…”
Section: Diagnosismentioning
confidence: 99%
“…Treatment with chemotherapy and younger age have also been associated with significantly higher overall survival in AEL [ 3 , 15 ]. A recent 2023 retrospective analysis by Gera et al demonstrated an inverse relationship between age and OS in patients with AEL, with a median OS of 69, 18, 8, 3, and 1 month for age groups <18, 18–49, 50–64, 65–79, and 80+, respectively [ 15 ]. Pediatric AEL shows a distinct genomic profile, which could partially explain the more favorable outcomes in this age group [ 15 ].…”
Section: Treatments and Clinical Outcomesmentioning
confidence: 99%
See 2 more Smart Citations